INDIVIDUAL COMMUNITY CHARACTERIZATION RELATIONSHIP TO PARTICIPATION IN MANGROVE FOREST MANAGEMENT - Rahmat Safe'i; A Nizam Syahiib (Universitas Padjadjaran, 2023)
Mangrove forests as a potential natural resource have many benefits that make them managed and always utilized by the community. However, the current condition of mangrove forests is very concerning and has suffered damage, one of the causes of which is human activities and activities. This study aims to find out the relationship of individual characteristics of the community to participation in mangrove forest management. Respondents to this study were 35 people who were members of community groups in Margasari Village. The stages and methods carried out in this study are: determination of the weight and score of individual characteristics of community and community participation using the Likert scale method with questionnaire instruments; and analysis of the relationship of individual characteristics of community to participation using the spearman rank method. The results showed that the community has actively carried out mangrove forest utilization and management activities in Margasari Village. This can be seen in the conditions of individual characteristics of community. People who are of productive age can carry out and carry out a job and activities optimally. In addition, the level of community activity can be seen in 90% of respondents who were educated last at the high school level, which shows that the mindset, absorption, and knowledge related to mangrove forests and their management are quite good. This study concludes that the individual characteristics of community do not indicate a close and significant relationship to community participation. Thus, the changes that occur in the individual characteristics of the community will not change the pattern of community activities and activities in the management of mangrove forests in Margasari Village.